FAKTOR RISIKO IBU BERSALIN YANG MENGALAMI KETUBAN PECAH DINI DI RSUD BANGKINANG - Nia Aprilla (Universitas Pahlawan, 2018)
One of the highest causes of AKI is infection. Most infections are caused by the KPD on maternity. The incidence of KPD ranges from 10% of all pregnancies. At term pregnancy the incidence varies between 6-19%, whereas in preterm pregnancy the incidence is 2% of all pregnancies. The aim of the study was to determine the risk factors for maternal births with early ruptured membranes in Bangkinang Hospital in 2017. The design of this study was descriptive. The population in this study were all women who had premature ruptured membranes recorded in the medical record of Bangkinang Hospital, which numbered 55 people, with a sample of 55 women who had premature rupture of membranes. Sampling technique with total population. The data collection tool used is medical record data using a check list sheet. The analysis used is univariate analysis. The results of the study were found to be mostly in the risk category namely <20 and> 35 years old (58.18%), with multiparous parity (56.36%), had experienced KPD (58.18%) and were not pregnant (63, 64%). Based on the results of research on the description of risk factors for KPD in Bangkinang Hospital in 2017, it can be concluded that most women who experience premature rupture of membranes are at the age of risk, those aged <20 and> 35 years, non-risky multiparity, risky KPD history that is, having had KPD and multiple pregnancies is not at risk, namely not multiple pregnancy. It is expected that health workers will provide information about the risk factors for premature rupture of membranes, especially in pregnant women during an antenatal care visit.